180k views
5 votes
Convert to slope intercept form

-4/3 (x+1) =y-2

1 Answer

5 votes

Remember that slope-intercept form is the form:


y = mx + b


Let's use some operations to try to get our current equation to that form:


- (4)/(3) (x + 1) = y - 2

  • Set up


- (4)/(3) x - (4)/(3) = y - 2

  • Distribute the
    - (4)/(3) onto
    (x + 1) using the Distributive Property


y = - (4)/(3)x + (2)/(3)

  • Add 2 to both sides of the equation

Our answer is
\boxed{y = - (4)/(3)x + (2)/(3)}.

User Janaye
by
6.2k points